Ballet and Beer: Discursive Multiplicity Mediated by Text. (17th September 2015) - Clark, Caroline Sutton
Abstract : Through the focus of historical inquiry into the monthly performances of Austin Ballet Theatre in Austin, Texas, a local amateur company, at the Armadillo World Headquarters, a psychedelic and "outlaw country" music hall, from 1972–1980, this paper explores an example of dance phenomena surviving outside of normative discursive support through the textual mediation provided by specific newspaper reviewers. The frequency and unique nature of these ballet performances created the circumstances that generated a more open, reciprocal, and diachronic conversation between the participants involving dance and text—a conversation that generated functioning narratives of identity.